A influência do ICMS Substituição no comércio varejista de calçados na Região do Cariri mediante regime de arrecadaçaõ tributária - Oliveira, Josefa Jocelma Amorim de (2012)
This work entitled "The Influence of ICMS Substitution in the retail shoe in Cariri by Tax Collection Scheme” aims to analyze the effect of the tax substitution in the footwear industry retail comparing this with the clothing retail business where there was no tax replacement. The econometric methodology used was the model "Difference in Difference" by ordinary least squares applied to the footwear sector (treatment group) which actually suffered the impact of TS in comparison to the garment sector (control group) was not exposed to TS. The database used in this study consisted of 2.237 billing observations, revenue from ICMS, and CNAE regime collapsed in the period 2004 to 2010 obtained from the Finance Department of the State of Ceará (SEFAZ) for Cariri in segment retail footwear and apparel. As result, in general, it has been seen that the tax replacement induced a R$10.771,77 (average values per company) raise in the collection of the ICMS for the footwear retail segment in Cariri. Specifically, the impact of the TR has floated depending on the company size, for instance, there hasn’t been a significant impact to micro single entrepreneur (MEI) neither for small size companies and for companies in the special scheme of supervision (ESP), but there has been a significant impact for micro companies (ME), valued at R$ 4.548,89 and for normal size companies (NL), valued at R$ 24.586,17.